Pengaruh Kepemilikan Institusional, Profitabilitas Dan Ukuran Perusahaan Terhadap Corporate Social Responsibility pada perusahaan Investasi Yang Terdaftar Di Bursa Efek Indonesia Periode 2016-2018 - Sri Patmawati; Zulkarnain (Jurnal Ilmiah Cano Ekonomos, 2020)
The purpose of this study was to determine the effect of institutional ownership, profitability and company size on social responsibility on investment companies listed on the Indonesia Stock Exchange in the 2016-2018 period. The object of this research is a Listed Investment company on the Indonesia Stock Exchange from 2016 to 2018. The analysis model used is multiple regression analysis. The results of this study indicate that partially institutional ownership has a significant effect on social responsibility, while profitability and company size do not significantly influence social responsibility, simultaneously institutional ownership, profitability and company size have a significant effect on social responsibility on investment companies listed on the Stock Exchange Indonesia Period 2016-2018. With the value indicated by a significance value of 0.026 <0.05 and an F-count value of 3.724 ≥ F-table of 3.028. Future research, it is better to do the addition of variables so that it can be known whether other variables that affect the company's corporate social responsibility.